Air inclusions in the polymer melt functioning as intrinsic physical blowing agents for the generation of foams in rotational molding. Issue 1 (January 2021) - Werner, Jannik; Vetter, Lukas; Hertle, Sebastian; Wolf, Michael; Drummer, Dietmar
In recent years, foams have experienced a major economic uprise, not least due to their lightweight construction potential. In this article, a new process variation is presented, which enables the generation of foamed structures in rotational molding by the utilization of vacuum. The novel method is based on entrapped air in the melt as an intrinsic physical blowing agent. By applying negative pressure in the cooling or solidification phase, the air bubbles expand. The crystallization freezes the existing conditions and thus forms the foamed structure. The investigations presented consider influences by different pressures as well as the temperature at which the vacuum is applied. The results with polyethylene show that by varying the pressure as well as the application temperature of the vacuum, components with different densities and cell characteristics result. The resulting foamed components excel by an improved stiffness per unit weight ratio.